2021
DOI: 10.1108/emjb-02-2021-0026
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of firm-specific and environmental-specific factors on short and long-term firm survival during an economic crisis

Abstract: PurposeLooking back on the last 12 years, the whole planet went through two major economic crises (2008 and 2019), which both had a profound impact on the survival of businesses. The present study aims to develop and empirically test a conceptual framework that investigates the factors that have an influence on firm survival. More specifically, the study proposes a three-dimensional framework that includes performance drivers (utilizing resource-based view [RBV] factors), performance measures and the measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 152 publications
0
8
0
Order By: Relevance
“…Esteve-Pérez and Mañez-Castillejo suggest that a firm’s ability to develop resources enhances its ability to adapt to a changing competitive environment and improves its survival prospects [ 21 ]. Chatzoudes et al’s findings show the indirect impact of RBV factors on a company’s long-term survival during an economic crisis [ 22 ]. Mayr et al show the desirability of applying RBV assumptions in the context of crisis-affected companies [ 23 ].…”
Section: Theoretical Underpinnings Of Abilities For Survivalmentioning
confidence: 99%
“…Esteve-Pérez and Mañez-Castillejo suggest that a firm’s ability to develop resources enhances its ability to adapt to a changing competitive environment and improves its survival prospects [ 21 ]. Chatzoudes et al’s findings show the indirect impact of RBV factors on a company’s long-term survival during an economic crisis [ 22 ]. Mayr et al show the desirability of applying RBV assumptions in the context of crisis-affected companies [ 23 ].…”
Section: Theoretical Underpinnings Of Abilities For Survivalmentioning
confidence: 99%
“…Previous analyses also include an assessment of the factors that helped companies to overcome the crises they faced. Thus, regarding the economic crisis of 2008–2009, the following factors have helped companies to be more resilient: the innovation and the entrepreneurial spirit of the managers as main characteristics of the management [ [46] , [47] , [48] ]; the ability to diversify and expand into new areas of business in order to compensate for low demand [ 49 ] or issues related to manufacturing capacity (“manufacturing-marketing alignment”, “manufacturing capabilities”) [ 50 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While Lai and Wong (2020) used the term crisis management strategies to denote the ways in which business organizations react to unexpected and negative situations that threaten their survival, profitability and sustainability, other researchers Ogbu (2018) and Chatzoudes et al, 2021, used the term survival strategies. Previous studies have defined survival practices in different ways.…”
Section: Business Survival Strategiesmentioning
confidence: 99%
“…According to Spaliara and Tsoukas (2013) firm characteristics could be considered as the first determinant of firm survival. Chatzoudes et al (2021) investigated the impact of firm and environmental specific factors on short and long-term firm survival during an economic crisis and found that manufacturing-marketing alignment, manufacturing capabilities, structural configuration and business performance under crisis have the most significant impact and on short-term survival. In contrast, competitive advantage and business performance under crisis have the most significant impact on long-term survival.…”
Section: Business Survival Strategiesmentioning
confidence: 99%